Intravenously Injected Mesenchymal Stem Cells Penetrate the Brain and Treat Inflammation-Induced Brain Damage and Memory Impairment in Mice - Lykhmus, Olena; Koval, Lyudmyla; Voytenko, Larysa; Uspenska, Kateryna; Komisarenko, Serhiy; Deryabina, Olena; Shuvalova, Nadia; Kordium, Vitalii; Ustymenko, Alina; Kyryk, Vitalii; Skok, Maryna (Frontiers in Pharmacology, 2019)
Neuroinflammation is regarded as one of the pathogenic factors of Alzheimer disease (AD). Previously we showed that mice regularly injected with bacterial lipopolysaccharide (LPS) possessed the AD-like symptoms like episodic memory decline, elevated amounts of amyloid beta (Aβ) peptide (1-42) and decreased levels of nicotinic acetylcholine receptors (nAChRs) in the brain. The use of mesenchymal stem cells (MSC), which can differentiate into multiple cell types, including neurons, is an attractive idea of regenerative medicine, in particular, for neurodegenerative disorders like AD. In the present study, we aimed to investigate whether pathogenic effect of LPS on the brain and behavior of mice can be prevented or treated by injection of MSCs or MSC-produced soluble factors. Fluorescently-labeled MSCs, injected intravenously, were found in the brain blood vessels of LPS-treated mice. Mice co-injected with LPS and MSCs did not demonstrate episodic memory impairment, Aβ(1-42) accumulation and nAChR decrease in the brain and brain mitochondria. Their mitochondria released less cytochrome c under the effect of Ca2+ compared to mitochondria of LPS-only-treated mice. Moreover, MSCs could reverse the pathogenic symptoms developed 3 weeks after LPS injection. Cultured MSCs produced IL-6 in response to LPS and MSCs effect in vivo was accompanied by additional stimulation of both micro- and macroglia. Xenogeneic (human) MSCs were almost as efficient as allogeneic (mouse) ones and regular injections of human MSC-conditioned medium also produced positive effect. These data allow suggesting MSCs as a potential therapeutic tool to cure neuroinflammation-related cognitive pathology.